Evaluasi Program Seleksi Di Sekolah “XM” Dengan Metode Evaluasi CIPP - Yosua Hoggy Parulian Purnomo; Thomas Budi Santoso (Universitas Katolik Soegijapranata, Semarang, 2020)
This research is an evaluation research which aims to determine the implementation of the teacher selection program that has been taking place and to find out what improvement needed in the teacher selection program. The evaluation method used is the CIPP evaluation (Context, Input, Process, Product). Researchers evaluated the psychotest, interviews, microteaching and decision making activities with CIPP. The results of this study indicate that the interview and microteaching activities have not achieved their goals. Its necessary to make improvement to the : teacher standards needed by school, interview instruments, microteaching instruments and interview training for the interview officers.